Teaching Maritime English to ESP Learners Through Moodle Platform (LITPAM, 2025)
This study aimed to evaluate the impact of Moodle as a virtual learning platform on oral communication skills of Iranian seafarers as ESP (English for Specific Purposes) learners. The study collected quantitative data using a quasi-experimental design. Participants in the study were 30 Iranian seafarers, divided into two groups of 15 people in the control and experimental groups. As part of their job requirements, as mariners, participants were required to practice maritime English. The researchers used Moodle as a virtual learning platform and compared participants' pre- and post-treatment results to determine the impact of the platform on their learning outcomes. To help seafarers improve their oral communication skills at sea or offshore, participants in both groups were taught a few chapters of standard marine communication phrases. During the first week of the five-week course, students learned how to use Moodle. Treatment was done in three weeks and evaluation was done in the last week. The results showed a significant improvement in participants' maritime English oral communication skills via Moodle. The study suggests that Moodle can be an effective tool for ESP learners. Due to its practicality, easy accessibility and versatile functionality, the researchers propose using the Moodle virtual learning environment for the development of fully online-based ELT courses.